Implementation of Electronic Word of Mouth (E-WOM) In Shaping The Brand Image of Avoskin Beauty - Nabilah Syaharani; Khaerudin Imawan; Yanto Heryanto (Interaction Communication Studies Journal, 2026)
Brand image builds customer trust, particularly in social media, where open interaction between brands and consumers is encouraged. In the ever-faster flow of information, customers are no longer only the recipients of messages but also share information through Electronic Word of Mouth (E-WOM), especially in the skincare industry. Reviews, user experience, and digital recommendations from E-WOM influence how consumers perceive a brand. This phenomenon is present in Avoskin Beauty, where customer interactions on Instagram show how an individual’s personal experience can affect overall brand perception. The data were collected through in-depth interviews with a descriptive qualitative method. To analyze the effect of digital interactions on brand image formation, the analysis focused on the dimensions of intensity, content, and credibility of E-WOM. The results of the research show that the quality of information in E-WOM, such as honesty and relevance, is more important than the number of interactions. The brand values promoted, and the community participation, too, contribute to the consumer perceptions. Therefore, E-WOM could be a strategic element in the construction of a strong brand image through continuous social interaction on digital media.